Alloy material of pet and pvc and its preparation method
Patent Information
- Application Number
- CN202210653706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-06-10
AI Technical Summary
[0024]Invention Principle: This invention uses diols containing methoxy groups in their side chains to prepare PET materials. Due to the polar interaction between the oxygen-containing polar groups and the polar Cl groups in the side chains of PVC, the resulting PET material has good compatibility with PVC. In addition, this invention uses hydrogenated bisphenol A to increase the glass transition temperature of the PET material and lower its melting point, allowing the PET material to be blended with PVC at lower processing temperatures. The resulting PET-PVC alloy material has good impact resistance, tensile properties, and strength.
Smart Images

Figure CN117247526B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to alloy materials and their preparation methods, specifically to an alloy material of PET and PVC with excellent impact resistance, tensile strength, and strength properties, and its preparation method. Background Technology
[0002] Plastic alloys are materials formed by blending two or more plastics, combining the excellent properties of both materials and imparting new properties to the resulting alloy. However, due to the structural and property differences between various plastics, blending processes are difficult, resulting in alloys with poor performance that cannot be efficiently utilized.
[0003] The invention patent with publication number CN103304968 discloses an acid-resistant PET / PVC alloy material and its preparation method, comprising the following components by weight: 70-80 parts PET, 20-30 parts PVC, 10-15 parts polyethylene, 3-5 parts acrylonitrile-styrene copolymer, 3-5 parts polyoxymethylene, 5-10 parts hydroxyl silicone oil, 5-10 parts epoxy resin, 3-5 parts melamine-formaldehyde resin, 4-8 parts polytetrafluoroethylene, 3-9 parts aluminum hydroxide, 3-5 parts titanium dioxide, 7-10 parts nucleating agent, 2-8 parts crystallization promoter, 3-5 parts compatibilizer, 3-5 parts antioxidant, 2-3 parts UV stabilizer, 3-5 parts lubricant, 2-3 parts impact modifier, and 1-2 parts heat stabilizer. The PET / PVC material provided by this patent has a tensile strength of over 50 MPa and a flexural strength of over 80 MPa. Even after being subjected to corrosive damage from alkaline and acidic solutions, it still exhibits superior mechanical properties compared to conventional PET materials. The conventional PET used in this patent has a melting point of 250°C, which differs significantly from the melting point of PVC (PVC processing temperature 160°C), thus preventing normal plasticization between the two.
[0004] Patent CN104341698 discloses a method for preparing a PVC-PET alloy material based on modified microparticles. The steps are as follows: zinc fatty acid is heated, then silicon carbide powder is added, stirred evenly, and cooled to obtain a modified powder; the modified powder is then initially mixed with PVC in a mixer, followed by the addition of ethylene bis-stearamide and chlorinated polyethylene, heated and mixed evenly, and cooled to room temperature to obtain a preform; the preform, PVC, PET, alkyd resin, zinc oxide, cyclobutene terephthalate, tributyl phosphate, stabilizer, plasticizer, and coupling agent are mixed evenly, heated, held at that temperature, and cooled to obtain an alloy material powder; the alloy material powder is then extruded and granulated on a twin-screw extruder to obtain the final product. This patent achieves good coating between nanoparticles and polymers, resulting in an alloy material with excellent mechanical properties. However, the conventional PET used in this patent has a melting point of 250℃, which differs significantly from the melting point of PVC, preventing proper plasticization.
[0005] Therefore, solving the technical problems of poor compatibility and poor processing performance among various plastics is the key to preparing high-performance alloy materials. Summary of the Invention
[0006] Purpose of the invention: In order to solve the technical problems existing in the prior art, the present invention aims to provide an alloy material of PET and PVC with excellent compatibility and good processing performance. The present invention also provides a method for preparing the alloy material of PET and PVC.
[0007] Technical solution: The PET described in this invention has a melting point below 150°C and a glass transition temperature above 70°C, and its general structural formula is as follows:
[0008]
[0009] Where X, Y, and Z are positive integers.
[0010] Furthermore, the PET is polymerized from hydrogenated bisphenol A, a methoxydiol, terephthalic acid, ethylene glycol, and an antimony catalyst.
[0011] Furthermore, the methoxy-containing diol is selected from one of 2-methoxy-1,3-propanediol, 2-methoxy-1,4-butanediol, 2-methoxy-1,3-butanediol, or 3-methoxy-2,4-pentanediol.
[0012] Furthermore, the molar content of methoxydiol accounts for 18-28% of the total molar content, the molar content of hydrogenated bisphenol A accounts for more than 6% of the total molar content, and the alcohol-acid ratio is 1.5-1.7.
[0013] Furthermore, the antimony catalyst is selected from antimony glycolate, antimony acetate, or antimony trioxide.
[0014] The PET preparation method of the present invention involves stirring and pulping all raw materials together, controlling the esterification temperature at 200-260℃, ending the esterification when the amount of water produced reaches the theoretical amount, depressurizing to atmospheric pressure, reducing the pressure and raising the temperature to enter the high vacuum polycondensation stage, with the vacuum below 100Pa and the polycondensation temperature controlled at 270-290℃, and discharging the material after the stirring current reaches the rated value to obtain PET.
[0015] Furthermore, the specific operation of the PET preparation method is as follows: all raw materials are stirred and pulped together, purged with nitrogen three times, and then heated. The esterification temperature is controlled at 200-260℃ and the esterification pressure is 2.5MPa. When the amount of water produced by esterification reaches the theoretical amount, the esterification is ended, the pressure is released to atmospheric pressure, and the temperature is raised for 45 minutes under reduced pressure until it reaches above 270℃, entering the high vacuum polycondensation stage. The vacuum is below 100Pa, and the polycondensation temperature is controlled at 270-290℃. When the stirring current reaches the rated value, the material is discharged to obtain PET.
[0016] The PET and PVC alloy material of the present invention comprises, by weight: 40-60 parts PET, 40-60 parts PVC, 4-6 parts alkyd resin, 1-3 parts zinc oxide, 4-6 parts triethyl phosphate, 2-4 parts stabilizer, and 2-4 parts plasticizer.
[0017] Furthermore, the stabilizer is an organotin compound.
[0018] Furthermore, the plasticizer is dioctyl phthalate.
[0019] The preparation method of the PET and PVC alloy material of the present invention comprises the following steps:
[0020] (1) Mix PET, PVC, alkyd resin, zinc oxide, triethyl phosphate, stabilizer and plasticizer evenly by weight, and then heat and keep warm.
[0021] (2) Add the above mixture into a twin-screw extruder and granulate it to obtain an alloy material of PET and PVC.
[0022] Furthermore, in step (1), the temperature is raised to 90-110℃.
[0023] Further, in step (2), the extruder operating conditions are: main machine speed 180-220 r / min, pressure 10-15 MPa, and operating temperature: from the feed port to the die head, zone 1 temperature 100-120℃, zone 2 temperature 130-140℃, zone 3 temperature 140-150℃, and zone 4 temperature 150-160℃.
[0024] Invention Principle: This invention uses diols containing methoxy groups in their side chains to prepare PET materials. Due to the polar interaction between the oxygen-containing polar groups and the polar Cl groups in the side chains of PVC, the resulting PET material has good compatibility with PVC. In addition, this invention uses hydrogenated bisphenol A to increase the glass transition temperature of the PET material and lower its melting point, allowing the PET material to be blended with PVC at lower processing temperatures. The resulting PET-PVC alloy material has good impact resistance, tensile properties, and strength.
[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: By preparing low-melting-point PET materials, the compatibility with PVC materials is significantly improved, the processing temperature is reduced, and the processing difficulty of low-melting-point PET and PVC alloy materials is reduced. The resulting alloy materials have excellent comprehensive performance, with excellent impact resistance, tensile properties and strength, high hardness, and good hydrolytic stability. Compared with pure PET, the tensile strength of the PET and PVC alloy materials prepared by the present invention is increased by 52%, the impact strength at 23℃ is increased by 93%, the impact strength at -20℃ is increased by up to 58%, the flexural strength is increased by 53%, the elongation at break is increased by 31%, and the hardness can reach above 50. Attached Figure Description
[0026] Figure 1 This is a cross-sectional SEM image of the alloy material obtained in Example 1 of the present invention at 5000x magnification. Detailed Implementation
[0027] The present invention will now be further described with reference to specific embodiments.
[0028] Example 1: The preparation method of the alloy material of PET and PVC is as follows:
[0029] (1) Preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 62 g of 2-methoxy-1,3-propanediol (CAS No.: 761-06-8), 49.5 g of hydrogenated bisphenol A, and 150 g of ethylene glycol were added to a 2L reactor. The alcohol-acid ratio was 1.52. The mixture was stirred and slurried. After nitrogen purging three times, the temperature was raised. Esterification reaction was carried out at 260℃ and 2.5 MPa (gauge pressure). When the water output reached the theoretical value, the esterification was stopped and the pressure was released to normal. The temperature was gradually raised to enter the low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 290℃. The material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 148.6℃, a glass transition temperature Tg of 75.6℃, an intrinsic viscosity of 0.662 dL / g, and a terminal carboxyl group of 28 mol / t.
[0030] (2) Take 50 kg of low melting point PET obtained in step (1) and mix it with 50 kg of PVC, 5 kg of alkyd resin, 2 kg of zinc oxide, 5 kg of epoxy resin, 5 kg of triethyl phosphate, 3 kg of dibutyltin dilaurate and 3 kg of dioctyl phthalate. Then heat it to 100℃ and keep it warm for 30 min.
[0031] (3) The above mixture is extruded and granulated on a twin-screw extruder with a main extruder speed of 200 r / min, a pressure of 12 MPa, and an operating temperature of 110°C in zone 1, 135°C in zone 2, 145°C in zone 3, and 155°C in zone 4 from the feed port to the die head to obtain an alloy material of PET and PVC.
[0032] like Figure 1 The SEM image (5000x magnification) of the cross-section of the alloy sample shows that the interface between the PET and PVC phases is not clear and is blurred, indicating that the two phases are compatible. Furthermore, after the sample has been repeatedly bent more than ten times, there is no obvious separation between PVC and PET in the cross-section.
[0033] Example 2: The difference from Example 1 lies in the preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 103 g of 2-methoxy-1,3-propanediol, 74.5 g of hydrogenated bisphenol A, and 140 g of ethylene glycol were added to a 2L reactor with an alcohol-acid ratio of 1.68. The mixture was stirred and slurried, purged with nitrogen three times, and then heated to 200°C and 2.5 MPa for esterification. When the water output reached the theoretical value, the esterification was stopped, the pressure was released to atmospheric pressure, and the temperature was gradually increased to enter a low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 270°C, and the material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 133°C, a glass transition temperature (Tg) of 71.9°C, an intrinsic viscosity of 0.682 dL / g, and 39 mol / t of terminal carboxyl groups.
[0034] Example 3: The difference from Example 1 lies in the preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 82 g of 2-methoxy-1,3-propanediol, 66 g of hydrogenated bisphenol A, and 150 g of ethylene glycol were added to a 2L reactor with an alcohol-acid ratio of 1.65. The mixture was stirred and slurried, purged with nitrogen three times, and then heated to 240°C and 2.5 MPa for esterification. When the water output reached the theoretical value, the esterification was stopped, the pressure was released to atmospheric pressure, and the temperature was gradually increased to enter a low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 280°C, and the material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 140.3°C, a glass transition temperature (Tg) of 72.8°C, an intrinsic viscosity of 0.670 dL / g, and 32 mol / t of terminal carboxyl groups.
[0035] Example 4: The difference from Example 1 lies in the preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 90 g of 2-methoxy-1,3-propanediol, 60 g of hydrogenated bisphenol A, and 143.5 g of ethylene glycol were added to a 2L reactor with an alcohol-acid ratio of 1.62. The mixture was stirred and slurried, purged with nitrogen three times, and then heated to 220°C and 2.5 MPa for esterification. When the water output reached the theoretical value, the esterification was stopped, the pressure was released to atmospheric pressure, and the temperature was gradually increased to enter a low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 285°C, and the material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 141.3°C, a glass transition temperature (Tg) of 73.5°C, an intrinsic viscosity of 0.690 dL / g, and 36 mol / t of terminal carboxyl groups.
[0036] Example 5: The difference from Example 1 lies in the preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 83 g of 2-methoxy-1,3-propanediol, 70 g of hydrogenated bisphenol A, and 153.5 g of ethylene glycol were added to a 2L reactor with an alcohol-acid ratio of 1.68. The mixture was stirred and slurried, purged with nitrogen three times, and then heated to 240°C and 2.5 MPa for esterification. When the water output reached the theoretical value, the esterification was stopped, the pressure was released to atmospheric pressure, and the temperature was gradually increased to enter a low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 280°C, and the material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 140.6°C, a glass transition temperature (Tg) of 73.1°C, an intrinsic viscosity of 0.669 dL / g, and a terminal carboxyl group of 32.9 mol / t.
[0037] Example 6: The difference from Example 1 lies in the preparation of PET: 350 g of terephthalic acid, 0.13 g of antimony glycol, 64 g of 2-methoxy-1,4-butanediol, 48.0 g of hydrogenated bisphenol A, and 150 g of ethylene glycol were added to a 2L reactor with an alcohol-acid ratio of 1.523. The mixture was stirred and slurried, purged with nitrogen three times, and then heated to 240°C and 2.5 MPa for esterification. When the water output reached the theoretical value, the esterification was stopped, the pressure was released to atmospheric pressure, and the temperature was gradually increased to enter a low vacuum stage. After 45 min of low vacuum, the high vacuum polycondensation stage (vacuum < 100 Pa) was entered. The polycondensation temperature was 280°C, and the material was discharged when the stirring power reached the rated value. The synthesized PET had a melting point of 149.0°C, a glass transition temperature (Tg) of 75.0°C, an intrinsic viscosity of 0.660 dL / g, and 28 mol / t of terminal carboxyl groups.
[0038] Comparative Example 1: The difference from Example 1 is that low-melting-point PET was not added.
[0039] Comparative Example 2: The difference from Example 1 is that the diol used in the preparation of PET is 1,3-propanediol.
[0040] The alloy materials obtained in Examples 1-6 and Comparative Examples 1-2 were subjected to mechanical property tests: cantilever beam notched impact strength test standard ISO0180, tensile strength test standard ISO0527, elongation at break test standard ISO0527, and bending strength test standard ISO0178. The test results are shown in Table 1.
[0041] Table 1 Mechanical Performance Test Results
[0042]
Claims
1. An alloy material of PET and PVC, characterized in that, By weight, it comprises: 40-60 parts PET, 40-60 parts PVC, 4-6 parts alkyd resin, 1-3 parts zinc oxide, 4-6 parts triethyl phosphate, 2-4 parts stabilizer, and 2-4 parts plasticizer; the PET has a melting point below 150℃ and a general structural formula as follows: Wherein, X, Y, and Z are positive integers; the PET is polymerized from hydrogenated bisphenol A, a methoxydiol, terephthalic acid, ethylene glycol, and an antimony catalyst; the methoxydiol accounts for 18-28% of the total molar content, the hydrogenated bisphenol A accounts for more than 6% of the total molar content, and the alcohol-acid ratio is 1.5-1.7; the methoxydiol is selected from one of 2-methoxy-1,3-propanediol, 2-methoxy-1,4-butanediol, 2-methoxy-1,3-butanediol, or 3-methoxy-2,4-pentanediol.
2. The alloy material of PET and PVC according to claim 1, characterized in that, The PET preparation method is as follows: all raw materials are stirred and pulped together, the esterification temperature is controlled at 200-260℃, the esterification is ended when the amount of water produced by esterification reaches the theoretical amount, the pressure is released to normal pressure, the pressure is reduced and the temperature is increased to enter the high vacuum polycondensation stage, the vacuum is lower than 100Pa, the polycondensation temperature is controlled at 270-290℃, and the material is discharged when the stirring current reaches the rated value, thus obtaining PET.
3. The alloy material of PET and PVC according to claim 1, characterized in that, The stabilizer is an organotin compound.
4. The alloy material of PET and PVC according to claim 1, characterized in that, The plasticizer is dioctyl phthalate.
5. A method for preparing the alloy material of PET and PVC as described in claim 1, characterized in that, Follow these steps: (1) Mix PET, PVC, alkyd resin, zinc oxide, triethyl phosphate, stabilizer and plasticizer evenly by weight, and then heat and keep warm. (2) The above mixture is added to a twin-screw extruder and extruded and granulated to obtain an alloy material of PET and PVC.
6. The method for preparing the alloy material of PET and PVC according to claim 5, characterized in that, In step (1), the temperature is raised to 90-110℃.
7. The method for preparing the alloy material of PET and PVC according to claim 5, characterized in that, In step (2), the extruder operating temperature is as follows: from the feed port to the die head, the temperature in zone 1 is 100-120℃, the temperature in zone 2 is 130-140℃, the temperature in zone 3 is 140-150℃, and the temperature in zone 4 is 150-160℃.
Citation Information
Patent Citations
Highly transparent copolyester synthesized by biomass-resource-derived monomers and preparation method for highly transparent copolyester
CN102250330A
Acid corrosion resisting PET (Polyethylene glycol Terephthalate) / PVC (Polyvinyl Chloride) alloy material and preparation method thereof
CN103304968A
Method for preparing modified particle based PVC-PET alloy material
CN104341698A
High-temperature resistant modified copolyester
CN109929096A
Polyester resin composition, powder coating and workpiece
CN112566990A